1986
DOI: 10.1111/j.1365-2125.1986.tb02933.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic drug oxidation: pharmacokinetic basis and comparison of experimental indices.

Abstract: 1 The pharmacokinetic basis for using various experimental indices, (urinary drug: metabolite and metabolite:drug + metabolite ratios, urinary metabolite recovery and AUC values), for detecting polymorphic oxidative drug metabolism was examined. Pharmacokinetic determinants in addition to partial metabolic clearance down the polymorphic route were identified in each index. 2 The ability of the various indices to discriminate bimodality in population data was assessed using a computer simulation. 3 With the exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 16 publications
(26 reference statements)
0
43
0
Order By: Relevance
“…For example, the distribution of the area under the plasma drug concentration-time curve is usually positively skewed because this index is related inversely to the clearance of the drug. Similarly, the distribution of the urinary drug/metabolite ratio can be skewed dependent upon the means and variances of the renal and non-renal clearances of the parent drug (Jackson et al, 1986 puter simulation to explore the ability of these graphical methods to detect bimodality in frequency distributions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the distribution of the area under the plasma drug concentration-time curve is usually positively skewed because this index is related inversely to the clearance of the drug. Similarly, the distribution of the urinary drug/metabolite ratio can be skewed dependent upon the means and variances of the renal and non-renal clearances of the parent drug (Jackson et al, 1986 puter simulation to explore the ability of these graphical methods to detect bimodality in frequency distributions.…”
Section: Introductionmentioning
confidence: 99%
“…1-MU is the only metabolic product of 1-MX and this reaction is catalysed by xanthine oxidase (Birkett et al, 1983). The use of the ratio of product to substrate in urine collections, as an indication of the metabolic clearance of substrate, has been described previously (Jackson et al, 1986;Birkett et al, 1987). A further assumption, made when using this approach, was that allopurinol does not affect the renal clearance of 1-MU or 1-MX.…”
Section: Resultsmentioning
confidence: 99%
“…Peart et al (1986) have demonstrated an excellent correlation between DMR obtained by 4 h and 8 h urine collection. Jackson et al (1986) explored the pharmacokinetic basis of the urinary drug/metabolite ratio in a model drug with kinetic properties similar to that of D. They concluded that the time of urine collection would make little difference to the frequency distribution of the metabolic ratio. Table 1 shows that hourly sampling of urine was unable to provide adequate data for the calculation of the DMR in PM subjects.…”
Section: Discussionmentioning
confidence: 99%
“…With the small number of subjects studied it is not possible to infer from the present work whether phenotyping by a short urine collection, as suggested above, will result in a shift of the antimode. Jackson et al (1986) suggested that a change in the antimode would occur only when urine collection time was a small fraction of the elimination half-life of the parent drug. P.A.P.…”
Section: Discussionmentioning
confidence: 99%